Uncomplicated 90Y Selective Internal Radio Therapy in a Patient With Hepatocellular Carcinoma After Arterial and Portal Vein Embolizations. (March 2018) - van der Pol, Jochem; de Vos-Geelen, Judith; Bucerius, Jan; Mitea, Cristina; van der Leij, Christiaan
Abstract : Abstract: Selective internal radio therapy (SIRT) with 90 Y-glass microspheres was performed in a cirrhotic patient with hepatocellular carcinoma (Barcelona Clinic Liver Cancer stage C) after arterial coil embolization for treatment of intratumoral hemorrhage and planned preoperative right portal vein embolization. Three technetium 99m Tc macro-albumin-aggregate injections were needed to optimize intralesional uptake without extrahepatic deposition. The consecutive SIRT treatment was uncomplicated with a remarkable result.